Análise das políticas de permanência: estudo multicaso das Universidades federais do estado de São Paulo - Pinto, Flavia Patricia [UNIFESP] (2015)
The research addresses the student residence policy of the Federal Universities of São Paulo state and the management of funds from the National Student Assistance Program (PNAES), social policy created by the government to support students in socioeconomic vulnerability condition. The goal is to compare the implementation of the student conditions for permanence factors policies in the three federal state universities: Federal University of São Paulo (UNIFESP), Federal University of São Carlos (UFSCAR) and Federal University of ABC (UFABC). To achieve this objective we performed a multi case study with data collection conducted in two stages: through desk review the general characteristics were identified from the current adopted permanence policies and in the second phase, interviews were conducted with those responsible for the management of these policies in these universities to increase knowledge of its guidelines, impact of the process of expansion and development expenses in the period 2011 to 2014. It justified the relevance of this study by changes in access and expansion of higher education occurred in the last decade and to be modest contributions in the literature on the subject. To conduct the study were prepared four propositions possible to conclude on the remaining policies: the growing number of students in socioeconomic vulnerability in universities; While the funds received by PNAES are growing every year they are still insufficient to meet all the actions foreseen in the federal program; the food expenses, in whole or in part, are supported directly by the university, because of their high expense and universalizing character; outsourcing of university restaurants does not have higher expenditure than the own management.